1994
DOI: 10.1007/bf02257780
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative staging of rectal cancer by endoluminal ultrasound vs. magnetic resonance imaging

Abstract: We suggest that ELUS and MRI must be evaluated within the framework of established parameters when treatment modalities such as preoperative radiation therapy and local or radical surgical approach must be decided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
61
0
5

Year Published

1996
1996
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(66 citation statements)
references
References 18 publications
0
61
0
5
Order By: Relevance
“…Its overall accuracy before radiation ranges from 73% to 94% in T staging, and from 70% to 80% in N staging. Comparative studies found EUS very accurate in staging rectal cancer from 80% to 95%, compared to 65% to 75% for CT and 75% to 85% for MRI [6][7][8][9] . CT and MRI have proved disappointing for detecting small neoplastic lesions.…”
Section: Mezzi G Et Al Eus and Mri In Rectal Cancermentioning
confidence: 95%
See 1 more Smart Citation
“…Its overall accuracy before radiation ranges from 73% to 94% in T staging, and from 70% to 80% in N staging. Comparative studies found EUS very accurate in staging rectal cancer from 80% to 95%, compared to 65% to 75% for CT and 75% to 85% for MRI [6][7][8][9] . CT and MRI have proved disappointing for detecting small neoplastic lesions.…”
Section: Mezzi G Et Al Eus and Mri In Rectal Cancermentioning
confidence: 95%
“…Rectal EUS helps select a group with advanced locoregional disease (stage T3 or T4) in whom this preoperative treatment offers most benefit [3][4][5] . The accuracy of EUS in staging rectal cancer ranges from 80% to 95% compared to 65%-75% for computed tomography (CT) and 75%-85% for magnetic resonance imaging (MRI) [6][7][8][9] . There is still debate about the role of cross-sectional imaging to restage rectal cancer after RT-CT, and data are scanty on accuracy, sensitivity, and specificity rates, suggesting that these modalities are not efficient enough for restaging.…”
Section: Introductionmentioning
confidence: 99%
“…La resonancia magnética de pelvis presenta resultados similares a la ER en la etapificación del cáncer de recto 20,21 , en particular con el uso de la bobina endorectal 22,23 . Sin embargo en lesiones tumorales tempranas, la ER mantiene una ventaja respecto a la resonancia 24 .…”
Section: Discussionunclassified
“…This in part depends on the MRI technique, whether a surface (phasedarray) or an endo-rectal coil is used and is operator dependent. Satoh [21] found TRUS more accurate than MRI, while Thaler [22] and Waizer [23] found no difference between the two. In two recent prospective comparative studies there was no significant difference between TRUS and endo-rectal MRI in both T and N [24] ( Tables 2 and 3).…”
Section: Trans-rectal Ultrasound and Magnetic Resonance Imagingmentioning
confidence: 99%